الاهتمام الدولي بفئة المسنين و انعكاساته على التشريع الجزائري - مونية بن بو عبد الله; وردة بن بو عبد الله (My University, 2019)
International efforts have focused on the protection of the elderly, The United Nations Principles for Older Persons of 1991 implicitly include the rights of older persons at the international level, including independence, participation, care, self-actualization and dignity, as embodied in the International Covenant on Economic, Social and Cultural Rights,These efforts continued with the adoption of the second Madrid Action Plan on Aging in 2002, The Algerian legislator was affected by these efforts, which was clearly reflected by the issuance of a set of legal texts, including Law No. 12-10 on the protection of the elderly and Executive Decree No. 62-16 specifying the modalities of regulation of family and social mediation., To keep the elderly person in his family center